2014
DOI: 10.1073/pnas.1412489111
|View full text |Cite
|
Sign up to set email alerts
|

T-cell TGF-β signaling abrogation restricts medulloblastoma progression

Abstract: Cancer cell secretion of TGF-β is a potent mechanism for immune evasion. However, little is known about how central nervous system tumors guard against immune eradication. We sought to determine the impact of T-cell TGF-β signaling blockade on progression of medulloblastoma (MB), the most common pediatric brain tumor. Genetic abrogation of T-cell TGF-β signaling mitigated tumor progression in the smoothened A1 (SmoA1) transgenic MB mouse. T regulatory cells were nearly abolished and antitumor immunity was medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 63 publications
(79 reference statements)
1
47
0
1
Order By: Relevance
“…As such, after stimulation with polypeptide vaccines and Toll‐like receptor agonist‐based vaccines, CD8 effector T cells gain the expression of KLRG1 and secrete interferon‐γ (IFN‐γ) and tumor necrosis factor‐α (TNF‐α), which are critical for antitumor immunity . Suppression of the proliferation and functional status of these KLRG1 + immune effector cells profoundly promotes cancer progression …”
Section: Se‐cad and Cancer Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, after stimulation with polypeptide vaccines and Toll‐like receptor agonist‐based vaccines, CD8 effector T cells gain the expression of KLRG1 and secrete interferon‐γ (IFN‐γ) and tumor necrosis factor‐α (TNF‐α), which are critical for antitumor immunity . Suppression of the proliferation and functional status of these KLRG1 + immune effector cells profoundly promotes cancer progression …”
Section: Se‐cad and Cancer Progressionmentioning
confidence: 99%
“…61,62 Suppression of the proliferation and functional status of these KLRG1 1 immune effector cells profoundly promotes cancer progression. [63][64][65] Studies have shown that sE-cad is a ligand of KLRG1. The binding of sE-cad to KLRG1 on the surface of NK cells and T cells significantly inhibits antigen reactivity, cell proliferation and the production of TNF-a and other cytokines by effector immune cells in response to antigen stimulation.…”
Section: Se-cad Suppresses the Antitumor Immune Response By Binding Tmentioning
confidence: 99%
“…(C) We next sought to determine whether the isolated CD8 ϩ T cell populations were capable of mounting antitumor responses in vivo. To achieve this, we isolated CD8 ϩ T cells from transgenic mice expressing a dominant negative form of transforming growth factor beta (TGF-␤) receptor type II under CD4 promoter regulatory control (TGF-␤RII-DN) to promote infiltration of CD8 ϩ T cells into medulloblastomas (50). This dominant negative form retains the extracellular and transmembrane domains but has a truncated intracellular kinase domain, thereby allowing it to outcompete endogenous receptors for TGF-␤ ligands and blocking TGF-␤ signaling in CD4 ϩ and CD8 ϩ T cells (51).…”
Section: Fig 3 Isolation and Functionality Of Purified Cd8 ϩ T Cellsmentioning
confidence: 99%
“…Pilocytic astrocytomas (PAs) and ependymomas (EPNs) display some evidence of antitumor functions, with increased infiltration of immune cells including myeloid cells exhibiting a predominantly T‐cell‐activating phenotype . In contrast, pediatric GBM and MB contain fewer infiltrating immune cells, expressing markers associated with T‐cell inactivation (PD1) or suppression (Foxp3, TGF‐β, CD50, CD163, CD206) . However, immunohistochemistry and microarray data from separate cohorts of pediatric EPNs, high‐grade gliomas (HGGs), and MBs have shown associations between immune phenotypes and molecular tumor subgroup affiliation or patient outcome, suggesting substantial heterogeneity within each tumor type.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] In contrast, pediatric GBM and MB contain fewer infiltrating immune cells, expressing markers associated with T-cell inactivation (PD1) or suppression (Foxp3, TGF-, CD50, CD163, CD206). 14,17 However, immunohistochemistry and microarray data from separate cohorts of pediatric EPNs, 16,18 high-grade gliomas (HGGs), 19 and MBs 20 have shown associations between immune phenotypes and molecular tumor subgroup affiliation or patient outcome, suggesting substantial heterogeneity within each tumor type.…”
Section: Introductionmentioning
confidence: 99%